Effects of creatine supplementation on muscle power, endurance, and sprint performance - Izquierdo, M.; Ibanez, J.; Gonzalez-Badillo, J. J.; Gorostiaga, E. M. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: To determine the effects of creatine (Cr) supplementation (20 g.d[minus sign]1 during 5 d) on maximal strength, muscle power production during repetitive high-power-output exercise bouts (MRPB), repeated running sprints, and endurance in handball players. METHODS: Nineteen trained male handball players were randomly assigned in a double-blind fashion to either creatine (N = 9) or placebo (N = 10) group. Before and after supplementation, subjects performed one-repetition maximum half-squat (1RMHS) and bench press (1RMBP), 2 sets of MRPB consisting of one set of 10 continuous repetitions (R10) followed by 1 set until exhaustion (Rmax), with exactly 2-min rest periods between each set, during bench-press and half-squat protocols with a resistance equal to 60 and 70% of the subjects' 1RM, respectively. In addition, a countermovement jumping test (CMJ) interspersed before and after the MRPB half-squat exercise bouts and a repeated sprint running test and a maximal multistage discontinuous incremental running test (MDRT) were performed. RESULTS: Cr supplementation significantly increased body mass (from 79.4 +/- 8 to 80 +/- 8 kg; P < 0.05), number of repetitions performed to fatigue, and total average power output values in the Rmax set of MRPB during bench press (21% and 17%, respectively) and half-squat (33% and 20%, respectively), the 1RMHS (11%), as well as the CMJ values after the MRPB half-squat (5%), and the average running times during the first 5 m of the six repeated 15-m sprints (3%). No changes were observed in the strength, running velocity, or body mass measures in the placebo group during the experimental period. CONCLUSION: Short-term Cr supplementation leads to significant improvements in lower-body maximal strength, maximal repetitive upper- and lower-body high-power exercise bouts, and total repetitions performed to fatigue in the Rmax set of MRPB, as well as enhanced repeated sprint performance and attenuated decline in jumping ability after MRPB in highly trained handball players. Cr supplementation did not result in any improvement in upper-body maximal strength and in endurance running performance.